Minat Belajar Siswa pada Mata Pelajaran Pondok di Pondok Pesantren Tarbiyah Islamiyah Koto Tinggi Pandai Sikek - Okta, Ade Riant; Rahmi, Alfi (TSAQOFAH, 2024)
This research is conducted based on the discovery of phenomena at the Tarbiyah Islamiyah Boarding School in Koto Tinggi Pandai Sikek, which indicates that there are still several students who lack interest in the pondok subjects. They prefer not to attend pondok subject classes, sleep during pondok subject classes, and have poor communication with pondok subject teachers. The objective of this research is to determine students' interest in pondok subjects at the Tarbiyah Islamiyah Boarding School in Koto Tinggi Pandai Sikek. This study is a descriptive quantitative research. The population consists of all students at the Tarbiyah Islamiyah Boarding School in Koto Tinggi Pandai Sikek, and the sampling technique used is stratified random sampling based on specific considerations. The sample in this study is 43 students of Madrasah Aliyah (MA). Data collection is done using a questionnaire distributed to 43 students, and the data is analyzed using statistical tests. The techniques used in this research include Validation Test, Reliability Test, and Statistical Test. The results of the research, based on the conducted statistical test, show that the overall average is 19.3 with a percentage of 76.5% and a standard deviation of 2.7. It can be concluded that students' interest in pondok subjects at the Tarbiyah Islamiyah Boarding School in Koto Tinggi Pandai Sikek is at a high level.